Analisis Manajemen Pelaksanaan Sekolah Minggu Buddha - Widia Darma (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The purpose of this research is to describe in depth the process of implementing the management of the Sekar Teratai Buddhist Sunday School (SMB). This research will use a qualitative research approach. The data collection techniques of this research will use observation, interview and documentation study techniques. The research procedure used in this study consisted of several research steps with the Robert case study method. The results of this study are 1) SMB does not have a good management plan, 2) the teaching and learning process has not been planned and structured in a measured and systematic manner, 3) the utilization of facilities and infrastructure has not been maximally carried out 4) Loyalty of administrators, teachers and parents is high. Keywords: Management, Non-Formal Education, Buddhist Sunday School.